Tas2R signaling enhances mouse neutrophil migration via a ROCK-dependent pathway - Kobayashi, Daichi; Watarai, Tomoya; Ozawa, Madoka; Kanda, Yasuhiro; Saika, Fumihiro; Kiguchi, Norikazu; Takeuchi, Arata; Ikawa, Masahito; Matsuzaki, Shinsuke; Katakai, Tomoya (Frontiers in Immunology, 2022)
Type-2 bitter taste receptors (Tas2Rs) are a large family of G protein-coupled receptors that are expressed in the oral cavity and serve to detect substances with bitter tastes in foods and medicines. Recent evidence suggests that Tas2Rs are also expressed extraorally, including in immune cells. However, the role of Tas2Rs in immune cells remains controversial. Here, we demonstrate that Tas2R126, Tas2R135, and Tas2R143 are expressed in mouse neutrophils, but not in other immune cells such as macrophages or T and B lymphocytes. Treatment of bone marrow-derived neutrophils from wild-type mice with the Tas2R126/143 agonists arbutin and D-salicin led to enhanced C-X-C motif chemokine ligand 2 (CXCL2)-stimulated migration in vitro, but this response was not observed in neutrophils from Tas2R126/135/143-deficient mice. Enhancement of CXCL2-stimulated migration by Tas2R agonists was accompanied by increased phosphorylation of myosin light chain 2 (MLC2) and was blocked by pretreatment of neutrophils with inhibitors of Rho-associated coiled-coil-containing protein kinase (ROCK), but not by inhibitors of the small GTPase RhoA. Taken together, these results demonstrate that mouse neutrophils express functional Tas2R126/143 and suggest a role for Tas2R126/143–ROCK–MLC2-dependent signaling in the regulation of neutrophil migration.